2017
DOI: 10.1039/c7cc04323f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of seminaphtho-phospha-fluorescein dyes based on the consecutive arylation of aryldichlorophosphines

Abstract: Seminaphtho-phospha-fluorescein (SNAPF), a phosphine-oxide-containing unsymmetric fluorescein dye, was synthesized based on the consecutive arylation of PhPCl, followed by Friedel-Crafts cyclization. The resulting SNAPF exhibited several attractive photophysical properties including an intense fluorescence in the NIR region and a large Stokes shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…For example, fluorescein, a xanthene dye, exhibits a fluorescence maximum at 510 nm, while phospha-fluorescein, a phosphine-oxide-containing fluorescein analogue, exhibits an emission maximum of 656 nm. 25 This example aptly illustrates the substantial impact of the phosphine oxide group on the electronic structure.…”
Section: Introductionmentioning
confidence: 93%
“…For example, fluorescein, a xanthene dye, exhibits a fluorescence maximum at 510 nm, while phospha-fluorescein, a phosphine-oxide-containing fluorescein analogue, exhibits an emission maximum of 656 nm. 25 This example aptly illustrates the substantial impact of the phosphine oxide group on the electronic structure.…”
Section: Introductionmentioning
confidence: 93%
“…To date, the only known structure based on four linearly fused six‐membered rings containing phosphorus heterocycle was reported by Fukuzawa, Yamaguchi et al in 2017 (Figure ) . The compound 33 represents an extended structure of the previously described phosphafluorescein 26 .…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
“…The cell‐permeable acetyl‐protected 25 , was utilized for staining HeLa cells showing no significant cytotoxicity. Two years later, Fukuzawa, Yamaguchi et al examined the photophysical properties and the biological utility of 25 modified with a 2,6‐dimethyl phenyl group the 10‐position (compound 26 , Figure ). However, no significant improvement neither of its photophysical properties nor of p K a values was observed.…”
Section: Phosphorus Heteroarenes: the Originmentioning
confidence: 99%
“…When compared to the synthesis of classical rhodamine dyes, insertion of phosphorous at the bridging position decreases the yield of the resulting fluorophore. 9,19,26 Additional synthetic challenges arise in the case of fluorescein (due to the increased electron withdrawing capacity of the phenol group) 10 and rhodol (due to the need to construct an asymmetric structure). 27,28 During our investigation of different synthetic routes, the Yamaguchi group reported the direct conversion of phosphine oxidecontaining rhodamines to rhodol and fluorescein via a hydrolytic deamination reaction under basic conditions (pH > 10).…”
mentioning
confidence: 99%
“…Building upon a previously described route for phosphine oxide fluorophores, we found that yields of NR rhodamines could be significantly increased by first treating 3-bromo-N,N-dimethylaniline with sec-butyllithium and exposing the resulting lithiated reagent to ethyl dichlorophosphite. 26 Subsequent oxidation with a 50% H 2 O 2 solution yielded the phosphinate-bridged intermediate (2, Scheme 1a). A subsequent Vilsmeier-Haack reaction was used to generate the key intermediate 3.…”
mentioning
confidence: 99%